Um estudo sobre as práticas cotidianas e a identidade da feira do produtor de Maringá - PR - Cabana, Rocío Del Pilar López (2014)
The everyday, life being lived, is often regarded as elements of routine and passivity. However, as pointed by Certeau (1998), there are many arts of doing, tactics and strategies, subtle practices that become even more evident when talking about identity. Unlike many approaches that address the organizational identity as central and permanent, in this work it has been seen as fragmented and transient. Given this perspective, my goal was to understand how the tactics and strategies in everyday life of workers at the Feira do Produtor de Maringá (Maringá Producer's Fair) were changing as the identity of the Fair changed in more than 30 years of existence. This qualitative research used as instrument a participant observation, oral history interviews and discourse analysis, to get into the history of the Fair, in the memories of the workers, in the formative discourses of identities and in the power relationships that structure the everyday life of this organization. I noticed that the Feira do Produtor de Maringá did not present a single and main identity, but instead of it is fragmented due to its various groups (producers and non-producers; technicians and workers; Brazilians and non-Brazilians; majorities and minorities; satisfied and unsatisfied groups, among others) which are differently identified with the organization and are created and recreated in its everyday life. And is precisely in everyday life where struggles happen to defend the identity positions within the fair, but these struggles are almost invisible to the viewer outside the organization, because it were overshadowed by the perceivable stability enforced by different instruments and disciplinary discourses that inhibit non congruent behaviors with the prescribed ones. Thus, I realized in the historical course of the Fair that in the beginning the disciplinary instruments were lighter, and so the tactics and strategies were also more connected to new knowledge, new experiences, new learning linked to the workers' activity. As the formalization of the fair increased and concomitantly their disciplinary tools, new tactics and strategies were created to prevent from these new instruments of control as well to ease the plight of repressed identities, which is emphasized in this new context. Thus, tactics and strategies, although being seen as resistance movements and small protests can also be understood as deviations to not accept imposed organizational identities.